Accidental detection of clinically silent compound heterozygous Hb D Punjab/Hb Q India while analyzing HbA1c by high performance liquid chromatography - Dhanani, Hiren J.; Sukhadiya, Mittal C.; Dhanani, Nandini H.; Kothia, Jaysukh D.; Tandel, Bharart D. (International Journal of Research in Medical Sciences, 2021)
HbA1c is routinely prescribed investigations for diagnosing and monitoring diabetes and high-performance liquid chromatography (HPLC) is preferred method which is also able to identify presence of hemoglobin variant. A case was encountered where presence of variant hemoglobin was indicated. On further investigation with three different instruments, diagnosis of compound heterozygous Hb D Punjab/Hb Q India was made. The chromatogram on Bio-Rad D10 showed Hb D Punjab (ααββHbD Punjab)-29.89% at 3.96 minutes retention time (RT), Hb Q India (ααHbQ Indiaββ) -9.5% with 4.45 minutes RT, hybrid of HbQ India/Hb D Punjab (ααHbQ IndiaββHbD Punjab)-6% with 4.66 minutes RT, Hb A2 (ααδδ) was 2.5% and Hb A (ααββ) was 52.2%. Analysis done on Bio-Rad variant V-II confirmed these findings. Analysis done on Sebia capillary electrophoresis revealed major peak of 50.9% in zone 9/Z(A) constituted by Hb A, second peak of 39.8% in zone 6/Z(D) constituted by co-elution of Hb D and Hb Q India, third peak of 8.8% in zone 3-4/Z(A2-C) constituted by co-elution of Hb A2 and hybrid of Hb D Punjab/Hb Q India and a fourth peak of 0.5% in zone 1 representing Hb A2HbQ India (ααHbQ Indiaδδ). Ideally variants detected while analyzing HbA1c should be further investigated for confirmation and result of which should be shared, discussed and the patient should be encouraged for screening of available family members for relevant variant hemoglobin. Combination of cation exchange HPLC and capillary electrophoresis in this case was sufficient to arrive at conclusion.